Effect of binary basicity on chromium occurrence in stainless steel slag - Zeng, Qiang; Li, Jianli; Ma, Guojun; Zhu, Hangyu (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
Comprehensive utilization of stainless-steel slag (SSS) is restrained due to the risk of Cr6+ leaching. Based on the studying the microstructure of synthetic slag (SS) containing Cr2O3 with XRD, SEM-EDS, and Image pro, the effect of binary basicity on the chromium occurrence in SSS was investigated. The results indicated that the binary basicity had a significant impact on the properties of spinel crystals. There was a positive correlation between the calcium content in spinel crystals and the SS basicity. The size of spinel crystals varied from large to small and the precipitation occurrence changed with the basicity increase. Furthermore, the chromium occurrences changed with the basicity. The chromium was produced in spinel crystals at lower basicity, but as the basicity increased to 3.0, the chromium precipitated as calcium chromate. In view of the relationship between the chromium leaching behavior and its occurrence, increasing basicity raised the Cr6+ leaching.